1981
DOI: 10.1128/jcm.13.2.258-265.1981
|View full text |Cite
|
Sign up to set email alerts
|

Detection of respiratory syncytial, parainfluenza type 2, and adenovirus antigens by radioimmunoassay and enzyme immunoassay on nasopharyngeal specimens from children with acute respiratory disease

Abstract: Four-layer antispecies radioimmunoassay (RIA) and enzyme immunoassay (EIA) procedures were developed for the detection of respiratory syncytial virus (RSV), parainfluenza type 2 virus, and adenovirus antigens in nasopharyngeal specimens from children hospitalized for acute respiratory disease. Polystyrene beads (RIA) or flat-bottomed polystyrene microtiter plates (EIA) were used as the solid phases, guinea pig anti-virus immunoglobulin were used as the captive antibodies, rabbit anti-virus immunoglobulin were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
3

Year Published

1986
1986
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(73 citation statements)
references
References 14 publications
2
68
0
3
Order By: Relevance
“…This last advantage eliminates the problems of storage and transport of the samples, as well as the diagnostic problems later in the course of illness. Recent studies have shown that the sensitivity and the specificity of ELISA and RIA were comparable to those obtained by the immunofluorescence tec]anique or by conventional isolation techniques (Minnich and Ray, 1980: Sarkkinen et al, 1981a: Sarkkinen et al, 1981b.…”
Section: Efficiency and Performance Of Rapid Diagnostic Testsmentioning
confidence: 81%
See 1 more Smart Citation
“…This last advantage eliminates the problems of storage and transport of the samples, as well as the diagnostic problems later in the course of illness. Recent studies have shown that the sensitivity and the specificity of ELISA and RIA were comparable to those obtained by the immunofluorescence tec]anique or by conventional isolation techniques (Minnich and Ray, 1980: Sarkkinen et al, 1981a: Sarkkinen et al, 1981b.…”
Section: Efficiency and Performance Of Rapid Diagnostic Testsmentioning
confidence: 81%
“…The validity of rapid diagnosis of respiratory tract viral diseases was tested by antigen detection in a pilot project during an outbreak in Berlin, during the winter of 1980. The RIAs and the ELISAs were performed according to the methods of Sarkkinen et al (1981aSarkkinen et al ( , 1981bSarkkinen et al ( , 1981c and Halonen et al (1983). The purpose of the study was to test the efficiency of a four-layer RIA or enzyme immunoassay, respectively, in comparison with conventional isolation techniques in the routine work of the laboratory with unselected clinical specimens.…”
Section: Efficiency and Performance Of Rapid Diagnostic Testsmentioning
confidence: 99%
“…(ii) ELISA. The ELISA for detection of antigens from RSVs; adenoviruses; parainfluenza viruses 1, 2, and 3; and influenza viruses A and B in NPAs was performed as previously described (14,24).…”
Section: Patients and Specimensmentioning
confidence: 99%
“…Certain serotypes are associated with epidemics of pneumonia, and other respiratory tract infections (39). Diagnosis of adenovirus infection was traditionally based on serology and virus isolation, but more recently, immunoassays directed against viral antigens have been used (40,41).…”
Section: Adenovirus (Ad)mentioning
confidence: 99%